Respuesta :

1. Determining the value of x and y:

Given equation(s):

  • [tex]y = 3x - 1[/tex]
  • [tex]3x + y = -7[/tex]

To determine the point of intersection given by the two equations, it is required to know the x-value and the y-value of both equations. We can solve for the x and y variables through two methods.

Method-1: Substitution method

Given value of the y-variable: 3x - 1

Substitute the given value of the y-variable into the second equation to determine the value of the x-variable.

[tex]\implies 3x + y = -7[/tex]

[tex]\implies3x + (3x - 1) = -7[/tex]

[tex]\implies3x + 3x - 1 = -7[/tex]

Combine like terms as needed;

[tex]\implies 3x + 3x - 1 = -7[/tex]

[tex]\implies 6x - 1 = -7[/tex]

Add 1 to both sides of the equation;

[tex]\implies 6x - 1 + 1 = -7 + 1[/tex]

[tex]\implies 6x = -6[/tex]

Divide 6 to both sides of the equation;

[tex]\implies \dfrac{6x}{6} = \dfrac{-6}{6}[/tex]

[tex]\implies x = -1[/tex]

Now, substitute the value of the x-variable into the expression that is equivalent to the y-variable.

[tex]\implies y = 3(-1) - 1[/tex]

[tex]\implies[/tex]     [tex]\ \ = -3 - 1[/tex]

[tex]\implies[/tex]     [tex]= -4[/tex]

Therefore, the value(s) of the x-variable and the y-variable are;

[tex]\boxed{x = -1}[/tex]   [tex]\boxed{y = -4}[/tex]

Method 2: System of equations

Convert the equations into slope intercept form;

[tex]\implies\left \{ {{y = 3x - 1} \atop {3x + y = -7}} \right.[/tex]

[tex]\implies \left \{ {{y = 3x - 1} \atop {y = -3x - 7}} \right.[/tex]

Clearly, we can see that "y" is isolated in both equations. Therefore, we can subtract the second equation from the first equation.

[tex]\implies \left \{ {{y = 3x - 1 } \atop {- (y = -3x - 7)}} \right.[/tex]

[tex]\implies \left \{ {{y = 3x - 1} \atop {-y = 3x + 7}} \right.[/tex]

Now, we can cancel the "y-variable" as y - y is 0 and combine the equations into one equation by adding 3x to 3x and 7 to -1.

[tex]\implies\left \{ {{y = 3x - 1} \atop {-y = 3x + 7}} \right.[/tex]

[tex]\implies 0 = (6x) + (6)[/tex]

[tex]\implies0 = 6x + 6[/tex]

This problem is now an algebraic problem. Isolate "x" to determine its value.

[tex]\implies 0 - 6 = 6x + 6 - 6[/tex]

[tex]\implies -6 = 6x[/tex]

[tex]\implies -1 = x[/tex]

Like done in method 1, substitute the value of x into the first equation to determine the value of y.

[tex]\implies y = 3(-1) - 1[/tex]

[tex]\implies y = -3 - 1[/tex]

[tex]\implies y = -4[/tex]

Therefore, the value(s) of the x-variable and the y-variable are;

[tex]\boxed{x = -1}[/tex]   [tex]\boxed{y = -4}[/tex]

2. Determining the intersection point;

The point on a coordinate plane is expressed as (x, y). Simply substitute the values of x and y to determine the intersection point given by the equations.

⇒ (x, y) ⇒ (-1, -4)

Therefore, the point of intersection is (-1, -4).

Graph:

Ver imagen IBrainlyExpertI